COVID-19 pandemic simulation in Perak by SIR model / Nurul Asyiqin Izzani Idrus - Idrus, Nurul Asyiqin Izzani (2022)
In this work, the Susceptible-Infected-Removed (SIR) epidemiological model of the COVID-19 pandemic was introduced in the Malaysia Movement Control Order (MCO). The proposed model is intended to provide accurate prescient data to the chiefs of the evaluation of general welfare and social estimates identified with COVID-19 pestilence. The SIR model MCO shows a pinnacle of disease on 10 April 2020, in 100 dynamic cases by early July 2020, in 10 dynamic cases by end-August 2020, and almost zero daily new cases by the end week of July 2020, with a total of 6562 contaminated cases. Results suggest that the present MCO has decreased overall the quantity of the powerless population and the total number of contaminated cases. The technique used in this investigation to fit the SIR model was discovered to be accurate in mirroring the information observed in the first place.